2022
DOI: 10.1038/s41598-022-08926-2
|View full text |Cite
|
Sign up to set email alerts
|

Cold sensitivity, functional disability and predicting factors after a repaired digital nerve injury

Abstract: To investigate self-reported cold sensitivity and functional disability after a repaired digital nerve injury. We identified 3204 individuals operated with digital nerve repair in the Swedish national quality registry for hand surgery (HAKIR). Patient-reported symptoms, including cold sensitivity and perceived disability, were examined using two questionnaires (HQ-8 and QuickDASH), three and 12 months postoperatively. Patients with diabetes (n = 48; 3%) were identified in the Swedish National Diabetes Register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
(86 reference statements)
3
9
2
Order By: Relevance
“…Neither age, nor sex, affected QuickDASH scores at 12 months, which also has been reported among individuals with a single digital nerve injury [ 20 ]. This is in contrast to previous studies, where lower age has been reported as a significant predictor of successful motor recovery [ 32 , 37 ].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Neither age, nor sex, affected QuickDASH scores at 12 months, which also has been reported among individuals with a single digital nerve injury [ 20 ]. This is in contrast to previous studies, where lower age has been reported as a significant predictor of successful motor recovery [ 32 , 37 ].…”
Section: Discussionmentioning
confidence: 80%
“…We found no differences in occurrence of concomitant injuries between men and women, which is in contrast to individuals with a single injury to a digital nerve, where men tend to suffer from more severe and multiple injuries [ 20 ]. This could be explained by the position of the major nerve trunks, which commonly lie deep to the flexor tendons on the volar aspect, depending on the level, where an injury to the median or the ulnar nerves needs to be deep enough to perch the nerve and therefore often involves a more extensive and complex injury regardless of sex.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations